2015
DOI: 10.1007/s38313-015-0023-9
|View full text |Cite
|
Sign up to set email alerts
|

Octane requirements of modern downsized boosted gasoline engines

Abstract: Octane Require ments of Modern Downsized Boosted Gasoline Engines Over the past 15 years, Shell has published the results of various studies which show that for modern downsized gasoline engines, a high research octane number (RON) increases engine efficiency in the regions of the operating range where combustion is limited by engine knock. However for a given level of RON there is no advantage to having a fuel with a high motor octane number (MON), and there can even be a disadvantage. This can be explained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…Gasoline fuels are widely used in automobiles powered by spark ignition (SI) engines. Stringent regulations on fuel economy and emissions are motivating engine downsizing and boosting [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gasoline fuels are widely used in automobiles powered by spark ignition (SI) engines. Stringent regulations on fuel economy and emissions are motivating engine downsizing and boosting [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the intake pressure (i.e., boosting) via turbocharging typically results in higher in-cylinder temperatures; however, by the use of intercooling and exhaust gas recirculation, the intake temperatures for a given pressure are lower resulting in increased engine efficiency [2,3]. In such modern engines, the conventional antiknock quality metrics of research octane number (RON) [4] and motor octane number (MON) [5] are less relevant.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant conditions relating to the anti-knock quality of fuel blends within engines are the temperature and pressure conditions experienced by the unburnt end gas, which in modern engines tends to be at lower temperatures than those in the RON test. Hence, the most appropriate way to describe the octane appetite is neither RON nor MON, but an extrapolation of RON/MON values to cooler conditions [14].…”
Section: Introductionmentioning
confidence: 99%
“…This can lead to the flawed conclusion that, as long as a high octane sensitivity is desired for fuel performance, their incorporation is detrimental. Boot et al [14] have indeed demonstrated that, from a statistical point of view, a higher paraffinic fraction leads to lower octane sensitivity, which leads to a lower Octane Index in modern turbocharged engines, which in the end leads to a lower fuel performance [15,16,17,18]. But the use of optimized blending laws, such as those described above, allowing to create synergistic effects with isoparaffins on RON and octane sensitivity, could radically change this conclusion.…”
Section: = (4)mentioning
confidence: 99%